Deposition Methods for Microstructured and Nanostructured Coatings on Metallic Bone Implants: A Review - Bailey Moore; Ebrahim Asadi; Gladius Lewis (Advances in Materials Science and Engineering)
A review of current deposition processes is presented as they relate to osseointegration of metallic bone implants. The objective is to present a comprehensive review of different deposition processes used to apply microstructured and nanostructured osteoconductive coatings on metallic bone implants. Implant surface topography required for optimal osseointegration is presented. Five of the most widely used osteoconductive coating deposition processes are reviewed in terms of their microstructure and nanostructure, usable thickness, and cost, all of which are summarized in tables and charts. Plasma spray techniques offer cost-effective coatings but exhibit deficiencies with regard to osseointegration such as high-density, amorphous coatings. Electrodeposition and aerosol deposition techniques facilitate the development of a controlled-microstructure coating at a similar cost. Nanoscale physical vapor deposition and chemical vapor deposition offer an alternative approach by allowing the coating of a highly structured surface without significantly affecting the microstructure. Various biomedical studies on each deposition process are reviewed along with applicable results. Suggested directions for future research include further optimization of the process-microstructure relation, crystalline plasma spray coatings, and the deposition of discrete coatings by additive manufacturing.